Effectiveness of ustekinumab dose escalation in Crohn's disease patients with insufficient response to standard‐dose subcutaneous maintenance therapy. Issue 1 (15th May 2020) - Kopylov, Uri; Hanzel, Jurij; Liefferinckx, Claire; De Marco, Davide; Imperatore, Nicola; Plevris, Nikolas; Baston‐Rey, Iria; Harris, Richard J.; Truyens, Marie; Domislovic, Viktor; Vavricka, Stephan; Biemans, Vince; et al.
Summary: Background: Ustekinumab is effective in Crohn's disease. However, a substantial proportion of patients will not respond or lose response to ustekinumab. The current evidence to support the effectiveness of dose‐optimisation for ustekinumab nonresponse is limited. Aim: To assess the effectiveness of dose escalation of ustekinumab. Methods: This was a multicentre retrospective cohort study. We included active Crohn's disease patients who received a standard‐dose intravenous induction and at least one subcutaneous ustekinumab 90 mg dose. All enrolled patients received dose escalation by either shortening the interval between the doses to every 4 or 6 weeks, intravenous reinduction or a combination of strategies. The primary outcome of the study was clinical response at week 16 after dose escalation. Results: A total of 142 patients (22 centres/14 countries) were included. The patients were dose‐escalated after a median treatment duration of 30 weeks. At week 16 from escalation, 73/142 (51.4%) responded to treatment, including 55/142 (38.7%) in clinical remission. Corticosteroid‐free remission was achieved in 6/34 (17.6%) patients on corticosteroids at the time of escalation; 118/142 (83%) continued treatment beyond week 16. Follow‐up data beyond week 16 were available for 74/118 (62.7%) patients. On the last follow‐up, 51/98 (52%) patients with available data responded to treatment, including 41/98 (42%) in clinical remission. Conclusions: Intensification of ustekinumab maintenance dosage was effective in over 50% of the patients. This strategy should be considered in patients who are nonresponsive to every 8 weeks ustekinumab maintenance dosing.